(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
As a stable personality pattern, cognitive styles are the distinctive temperament of learners, information processing techniques, traditional modes of thought and the exploration of new concepts. The current inspection explores the effect on academic skills of the most well-known field-dependent and field-independent cognitive style and multifactorial construction impulsivity. In this project, 200 college students (including both male and female) who responded to the Embedded Figures Test, The UPPS Impulsive Behavior Scale for group formation, were non-randomly chosen. The data analysis performed using ANOVA, t-test showed that in all components of academic skills, field-independent students are significantly better than field-dependent students, although no difference between the two classes was found for ’time management’ (p > 0.05). In reading comprehension, vocabulary, logical reasoning, numerical abilities and time management, current research has also empirically proven that ’non-impulsive’ mentees are substantially better than impulsive novices (p